THE INTEGRATION OF LOCAL FOOD AND TOURISM: A STRATEGIC APPROACH FOR ECONOMIC WELFARE AND SUSTAINABILITY - Michael Ricky Sondak; Sinar Dharmayana Putra; Kellen Feivel Wijaya; Khalia Vista Alaskania; Julia (RADJA PUBLIKA, 2024)
Indonesia’s long-term development strategies emphasize the crucial role of agriculture in ensuring food security and promoting economic growth. This study examines how a rural area in South Sulawesi can enhance its economy and foster sustainable food production by leveraging its abundant agricultural resources, including strawberries and various vegetables. By integrating local food systems with tourism, the region can reduce food waste and create value-added products, such as strawberry jam, fruit peel flour, and canned vegetables, thereby supporting economic resilience and sustainability. Although local rural businesses often face challenges such as limited access to finance and technology, they can benefit from sustainable, green economy-focused practices. This research highlights the importance of incorporating agricultural by-products and eco-friendly products into agritourism to promote local prosperity while preserving the environment. Using a qualitative approach, the study explores how combining food systems and tourism can generate new income, promote a circular economy, and encourage the use of locally sourced, sustainable products. The findings suggest that this rural area could serve as a model for sustainable tourism, where local food production boosts both economic vitality and environmental stewardship.